Ontogenetic variation of the odontophore of Luidia superba (Asteroidea: Paxillosida) and its taxonomic implications - De los Palos-Peña, Magdalena (2021)
Introduction: The sea star odontophore is the structure positioned between the paired oral ossicles, with which they articulate through proximal and distal processes. The internal anatomy structures may be used as taxonomic characters for a precise differentiation between species, so it is necessary to describe the structures variation throughout growth. Objective: To describe the odontophore shape and variation of Luidia superba A. H. Clark, 1917 from specimens of the Gulf of California deposited in the Echinoderm National Collection, ICML UNAM. Methods: A total of 735 specimens were examined to describe the external characters, from which 55 selected specimens, within a range of R = 14 mm and R = 210 mm, were dissected to extract the odontophores and analyzed with geometric morphometrics. Results: Scanning electronic microscopy (SEM) images of the odontophores showing the variations in shape throughout growth are presented. Differences in shape between size groups were confirmed with a Canonical Variables Analysis (P < 0.05). Conclusions: There are three main groups in this size ranges where specialization of the stereom can be observed through the ontogenetic series; the variation in shape of the odontophore shown here is a precedent for the use of internal anatomy as new taxonomic characters of identification.